A new transition metal-tellurite glass family: electrical and structural properties - Terny, Cintia Soledad (2015)
Glasses of composition 0.8 [xBaO.(1 - x)MgO]. 0.2TM.2TeO2 with TM: MoO3, WO3, V2O5 or Nb2O5 (x = mol content) were obtained by the melt quenching technique. Raman Spectroscopy, Density and Differential Scanning Calorimetry were used to infer their microscopic structure and electrical properties were studied using Impedance Spectroscopy. Some singularities in their electrical and structural properties appeared. Deviations from linearity as a function of alkaline-earth oxide modifier content were observed both on the electrical and structural properties. They were analyzed considering the intensity of the electrical field of the mix of alkaline earth cations which induced changes on the glassy matrix and the mixed alkaline-earth effect was considered. The observed relationships between their electrical and structural properties and the mix of alkaline earth cations were different according to the transition metal oxide present.